HSC Arts 12th Board ExamMaharashtra State Board
Share
Notifications

View all notifications

If y = e^ax. cos bx, then prove that (d^2y)/(dx^2)-2ady/dx+(a^2+b^2)y=0 - HSC Arts 12th Board Exam - Mathematics and Statistics

Login
Create free account


      Forgot password?

Question

If y = eax. cos bx, then prove that

`(d^2y)/(dx^2)-2ady/dx+(a^2+b^2)y=0`

Solution

y = eax. cos bx

`dy/dx=ae^(ax).cosbx-be^(ax).sinbx.........(i)`

`dy/dx=ay-be^(ax).sinbx`

`(d^2y)/(dx^2)=ady/dx-b(ae^(ax).sinbx+be^(ax).cosbx)`

`(d^2y)/(dx^2)=ady/dx-abe^(ax).sinbx-b^2e^(ax).cosbx`

`(d^2y)/(dx^2)=ady/dx-a(ay-dy/dx)-b^2y ` [Substituting beax sinbx from(i)]

`(d^2y)/(dx^2)=ady/dx-a^2y+ady/dx-b^2y`

`therefore (d^2y)/(dx^2)-2ady/dx+(a^2+b^2)y=0`

Hence Proved

  Is there an error in this question or solution?
Solution If y = e^ax. cos bx, then prove that (d^2y)/(dx^2)-2ady/dx+(a^2+b^2)y=0 Concept: Derivatives of Composite Functions - Chain Rule.
S
View in app×